Aircraft structures - Peery, David J. (Dover Publications, 2011)
"Still relevant 62 years after its initial publication, this legendary reference text on aircraft stress analysis is considered the best book on the subject. A knowledge of aerodynamics is a prerequisite for its discussions of basic structural theory and the application of the elementary principles of mechanics to the analysis of aircraft structures. 1950 edition"-- Provided by publisher.
"This Dover edition, first published in 2011, is an unabridged republication of the work originally published in 1950 by the McGraw-Hill Book Co. Inc., New York"--T.p. verso.
Keywords: Airframes.; elektronické knihy; electronic books